Life on Green Patches: Diversity and Seasonal Changes of Butterfly Communities Associated With Wastelands of the Post‐Industrial Central European City - Sylwia Pietrzak; Krzysztof Pabis (Ecology and Evolution)
ABSTRACT Urban wastelands are among the most neglected urban habitats. Our study demonstrated that those spatially restricted patches of vegetation are an important refuge for various species of butterflies. We have assessed the diversity, distribution patterns, and seasonal changes of butterfly communities based on two‐year (2019–2020), quantitative studies at 5 urban wastelands in a large post‐industrial city in Central Poland. Forty‐six species of butterflies were recorded in the city. We have noticed homogeneity of fauna, although all investigated sites were characterised by high diversity and co‐occurrence of species associated with different habitats (e.g., grasslands, woodlands). Most of the species were common in Central Poland, although we have also recorded the presence of more specialised butterflies. Bray–Curtis similarity analysis reflected mostly seasonal changes in species composition. Seasonal patterns were very similar at all investigated sites and during both seasons, pointing to relative stability. Urban wastelands hosted from 34 to 41 species. This pattern results from the high diversity of microhabitats and the co‐occurrence of various plant species at single sites, which is very important for plant‐dependent organisms like butterflies.